x(y^2+z)p-y(x^2+z)q=z(x^2-y^2)
Given
Lagrange's auxiliary equation of (1) are;
Choosing "(\\frac{1}{x}, \\frac{1}{y}, \\frac{1}{z})" as multipliers, we get
Integrating "\\frac{dx}{x}+ \\frac{dy}{y}+\\frac{dz}{z}=0" we get "xyz=c_1"
Choosing "(x,y,-1)" as multipliers, we have
Integrating "xdx+ydy-dz=0"
"\\therefore" the solution is the system of equations:
"x^2+y^2-2z=c_2"
Taking "t" as a parameter, the given equation of the straight line "x+y=0,z=1" can be put in parametric form "x=t,y=-t,z=1"
Using this,
"x^2+y^2-2z=c_2"
May be written as,
"2t^2-2=c_2"
Eliminating "t" from the equation we get,
Putting values of "c_1" and "c_2" , the desired integral surface is,
Comments
Leave a comment